1988
DOI: 10.1042/bj2560213
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of recombinant-derived granulocyte-colony stimulating factor (G-CSF)

Abstract: Human granulocyte colony-stimulating factor (G-CSF), and a mutant having a Ser for Cys substitution at residue 18 were produced in Escherichia coli strain W3110. About 60 mg of pure protein was obtained from 50 g of wet cells with a recovery of about 20%. The proteins were characterized physically and chemically, including determination of disulphide bonds, which were found to exist between residues 37-43 and 65-75. Cys-18 is not involved in disulphide bond formation and was substituted by Ser with no effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…A previous study in which Cys 18 was mutated to Ser demonstrated that Cys 18 is not required for bioactivity of hGCSF [60]. However, during folding of hGCSF, intermolecular disulfide bonds between two Cys 18 residues or Cys 18 and another Cys residue can occur in aggregates [61].…”
Section: Discussionmentioning
confidence: 98%
“…A previous study in which Cys 18 was mutated to Ser demonstrated that Cys 18 is not required for bioactivity of hGCSF [60]. However, during folding of hGCSF, intermolecular disulfide bonds between two Cys 18 residues or Cys 18 and another Cys residue can occur in aggregates [61].…”
Section: Discussionmentioning
confidence: 98%
“…This protein has five Cys residues that form two disulphide bonds between Cys37-Cys43 and Cys65-75, and another Cys18 a free Cys residue which is not involved in any disulphide bond formation (Wingfield, 1988). It is complicated to recover soluble protein from IBs related to initial recovery, solubilization, and renaturation steps, hence, fusion partners are commonly considered to obtain the soluble protein (Thatcher, 1990).…”
Section: Resultsmentioning
confidence: 99%
“…Post translational modification is not an issue for hG-CSF because O-glycosilated bond does not bind with receptor, so both of the wild-type and non-glycosylated mutant recombinant hG-CSF possess colony stimulating activities (Wingfield, 1988;Hill, 1993). However, the Oglycosilated bond has an important role to avoid aggregation, thus, hG-CSF is frequently produced in E. coli as inclusion bodies (Yamamoto, 2002;Dasari, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Kuga et al [7] described a procedure involving IB solubilization, refolding by dialysis and DEAE-Sepharose chromatography. A purification process based on size-exclusion chromatography (Sephacryl S-200), renaturation and CMSepharose with overall recovery of about 20% was reported by Wingfield et al [8].…”
Section: Introductionmentioning
confidence: 94%
“…Several methods based on multiple chromatographic steps have been reported for the purification of rhG-CSF [7][8][9].…”
Section: Introductionmentioning
confidence: 99%